The correlation of anxiety disorders and tension-type headache among medical students of Udayana University - Christine Kathy Putri Sari; Sri Yenni Trisnawati GS; Ida Ayu Sri Wijayanti; AA Bagus Ngurah Nuartha (Intisari Sains Medis, 2019)
Introduction: a Tension-type headache (TTH) is a headache that is commonly happened in almost two-thirds of the world population, especially in medical students. Psychosocial factors, such as anxiety, is often contributed to the incidence of a tension-type headache.Method: The research was using a cross sectional design study to prove the correlation of anxiety disorders and TTH in medical students. Samples were collected by a consecutive method from medical students on second semester, fourth semester, and sixth semesters of Udayana University study year 2017/2018. TTH was diagnosed based on Konsensus Nasional IV PERDOSSI 2013 and anxiety was scored by Hamilton Rating Scale for Anxiety (HARS). Lambda test was used to prove the correlation between anxiety disorders and TTH.Result: There were 300 subjects with dominant age was between 19-20 years old (60.7%) and mostly woman (56.7%). The proportion of TTH was 85.3% while anxiety disorders were 66.7%. The incidence of TTH was found more commonly happened in a subject with anxiety disorders (94.5%) and statistically significant (p=0.001) with weak correlation (r=0.153).Conclusion: These data show a correlation of anxiety disorders and TTH with weak correlation.